P691 Trends in diagnostic prevalence and treatment patterns of adult ulcerative colitis patients in the USA, 2007–2017. (25th January 2019) - Hunter, T; Naegeli, A; Dong, Y; Choong, C; Stefani-Hunyady, D
Abstract: Background: There has been much variation between epidemiological studies that report the prevalence of ulcerative colitis (UC). This study aimed to analyse the diagnostic annual prevalence rates and treatment patterns of UC patients in the USA (U.S) adult insured population from 2007 to 2017. Methods: Trends in UC prevalence were calculated for the 11-year period covering January 1, 2007 to December 31, 2017. Adult (18+ years old) UC patients were included in this retrospective analysis of medical and pharmacy claims data from the IBM Marketscan Commercial, Medicaid and Medicare-Supplemental Claims database. Prevalence was determined as having ≥1 UC diagnostic codes (ICD-9: 556.x; ICD-10:K51.x) within the calendar year. Patients with a Crohn's disease diagnosis (ICD9: 555.x; ICD-10: K50.x) were excluded. Prevalence rates in the database were determined and age- and gender-adjusted rates were projected to the U.S. population in 2017. Trends in treatment patterns were also analysed. Results: The UC adult prevalence increased from 0.25% to 0.39% from 2007 to 2017. The mean age between 2007 and 2017 ranged from 41.75–49.31 years. Consistently throughout the years, approximately half of the UC patients were male. Rates of use of biologics and corticosteroids increased, while rates of 5-ASA and opioids decreased. Immunomodulators remained stable (Figure 1). Conclusions: The prevalence of UC diagnosis codes increased between 2007 and 2017, and is projected to affect approximately 1 million US adults in 2017.